2012
DOI: 10.1103/physrevb.85.235458
|View full text |Cite
|
Sign up to set email alerts
|

Electronic compressibility of layer-polarized bilayer graphene

Abstract: We report on a capacitance study of dual gated bilayer graphene. The measured capacitance allows us to probe the electronic compressibility as a function of carrier density, temperature, and applied perpendicular electrical displacement D. As a band gap is induced with increasing D, the compressibility minimum at charge neutrality becomes deeper but remains finite, suggesting the presence of localized states within the energy gap. Temperature dependent capacitance measurements show that compressibility is sens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
111
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(126 citation statements)
references
References 38 publications
13
111
0
1
Order By: Relevance
“…28,31,42,45,[80][81][82] Nevertheless, an experimental observation of features related to next-nearest layer couplings should be possible in high-mobility samples including suspended graphene 69,[83][84][85][86] or graphene on a boron nitride substrate. 66,72,73,87 In fact, Landau level crossings in trilayer graphene were recently observed, 66 and they allowed the determination of Slonczewski-Weiss-McClure parameter values in remarkably close agreement with those of bulk graphite. 32,88 …”
Section: Discussionmentioning
confidence: 67%
“…28,31,42,45,[80][81][82] Nevertheless, an experimental observation of features related to next-nearest layer couplings should be possible in high-mobility samples including suspended graphene 69,[83][84][85][86] or graphene on a boron nitride substrate. 66,72,73,87 In fact, Landau level crossings in trilayer graphene were recently observed, 66 and they allowed the determination of Slonczewski-Weiss-McClure parameter values in remarkably close agreement with those of bulk graphite. 32,88 …”
Section: Discussionmentioning
confidence: 67%
“…Since then, the majority of experiments probing the band gap have used single or dual gate devices based on exfoliated bilayer graphene flakes [19,20]. The band gap has now been observed in a number of different experiments including photoemission [16], magnetotransport [20], infrared spectroscopy [55, 78-80, 129, 130], electronic compressibility [131,132], scanning tunnelling spectroscopy [133], and transport [19,31,[134][135][136][137][138][139].…”
Section: A Experimentsmentioning
confidence: 99%
“…Numerous experimental studies of electronic properties of bilayer graphene were recently reported in the literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . From prospective of potential applications, the appeal of bilayer graphene is that a gap can be opened and tuned by the gate voltage [6][7][8][9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Using the dual (top and back) gated structures allows to control both the gap and the carrier density independently [11][12][13][14][15] . For these structures, opening of a gap was demonstrated in temperature and bias dependencies of resistivity 11,12 , in bias dependence of capacitance 14,15 , as well as in strong-filed magnetotransport 13 . Measurements in magnetic field reported in the literature focused either on weak-field (B ∌ 0.1 T) domain in order to reveal weak localization 2 and universal conductance fluctuations 10 , or quantizing (B ∌ 10 T) fields 4,7,10,13,14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation